Transformational School Leadership in Challenging Contexts: Lessons from Indonesia's Eastern Periphery - Ruth Mandak; Yuni Astuti (Journal of Innovation and Research in Primary Education, 2026)
This qualitative case study investigated transformational leadership practices of school principals in improving learning quality at SMA Negeri 7 and SMA Negeri 2 Sorong Regency, Papua Barat Daya, Indonesia. Employing Bass and Avolio's four-dimensional framework, data were collected from 179 participants through semi-structured interviews, systematic observations, and document analysis over four months (September-December 2025). Data analysis followed Miles, Huberman, and Saldaña's interactive model with multiple validation strategies ensuring trustworthiness. Findings revealed comprehensive implementation of all transformational leadership dimensions—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—with contextual adaptations reflecting institutional maturity and local sociocultural realities. Principals demonstrated moral authority through personal commitment, articulated compelling visions motivating community engagement, fostered culturally-responsive pedagogical innovation despite resource constraints, and provided personalized support addressing teachers' contextual challenges. SMA Negeri 7 emphasized solidarity-building leadership through motivational and exemplary dimensions, while SMA Negeri 2 focused on capacity-enhancing leadership through intellectual stimulation and professional development. Both approaches yielded significant learning quality improvements evidenced by enhanced teacher performance, innovative teaching practices, and improved student outcomes including international competition success. The study extends transformational leadership theory by identifying context-specific mechanisms operating in peripheral educational settings, demonstrating that strategic leadership transforms environmental constraints into innovative opportunities. Findings inform policy development for principal preparation programs emphasizing contextually-grounded competencies essential for educational leadership in underserved regions.